Dansk atomkultur fra 1945 til 1963:Forestillinger om atomenergiens praktiske anvendelse i efterkrigstiden i Danmark - Nielsen, Aske Hennelund (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
”Danish Nuclear Culture 1945 to 1963” examines the cultural reception and adaptation of the practical application of nuclear energy in Denmark in the post-war period. This includes the imaginaries and visions of the future, that were the result of this reception and adaption, as well as some of the contemporary societal impacts, these nuclear imaginaries and visions of the future had. Danish historiography has so far only expressed limited interest in this cultural aspect of Danish history in the 20. century, however, new research is currently underway. Internationally, especially in the USA and Great Britain, a rising tradition of nuclear culture scholarship has shown many different areas where the cultural reception of nuclear energy has influenced and shaped societies. This dissertation represents the first systematic, empirical study of the ways in which nuclear energy has been received and adapted in the post-war period in a national Danish case. The dissertation is inspired by several theoretical and methodical concepts that have been developed in the international scholarship. The point of departure of the dissertation is a modified version of Jonathan Hogg’s Nuclear Culture definition from 2016. The dissertation uses the theoretical framework of Sociotechnical Imaginaries, developed by Sheila Jasanoff and San-Hyun Kim, in combination with the concepts of power, transnational circulation and history of knowledge, as well as media publics, to examine how imaginaries and visions of the future circulated in Danish Society in the post-war period. In relation to this, the focus of this dissertation is on five communities and their media publics in which there were prevailing nuclear imaginaries and visions of the future, namely the National Danish Media Public, Danish Science, Danish Business, the Antinuclear Weapons Groups and the National Security Actors. These communities received and adapted nuclear energy in different ways at different times, and depending on the prevailing social practices, norms, expectations as well as understandings and discourses, produced different imaginaries and visions of the future in their groups. The dissertation dedicates a chapter to each of these communities, except for the Antinuclear Weapons Groups and the National Security Actors that share a chapter. In the first chapter of the analysis, the National Danish Media Public from 1945 to 1963 is examined, and four main nuclear imaginaries are identified, namely nuclear energy as a source of propulsion, nuclear energy as an energy source, nuclear energy as a weapon and the imaginaries connected with radiation. This chapter also discusses some of the fundamental aspects of the way nuclear energy was received and adapted in the national Danish context. In the subsequent chapter, Danish Science is analyzed in the period from 1945 to 1955. After several years of internal debate, Danish Science archived a new consensus in the mid-1950s, which mandated that nuclear energy should primarily be used as an energy source in nuclear power plants. Following this, the next chapter examines Danish Business in the period from 1953 to 1963. After Danish Science achieved their new consensus, their imaginary of nuclear energy as an energy source was circulated to the Danish Business community in the mid-1950s, which attempted to convert this imaginary into real world applications. In the final chapter of the analysis, the Antinuclear Weapons Groups, the National Security Actors and the conditions for their debate in the National Danish Media Public in the early 1960s is discussed. Both groups tried to elevate their nuclear imaginaries to be the prevailing in Danish society, which led to a large public debate. This dissertation makes several contributions to the Danish post-war historiography. The dissertation has examined and documented several areas of Danish history, which have not previously been analyzed. Primarily, the dissertation contributes to the Danish historical scholarship with a new history of technology and cultural history approach that brings into focus the importance of reception and adaption of new technologies in different communities and groups, which can influence and change societal tendencies and development